Brand Gravity-Resonance Capability on Brand Love: a Resource-Advantage theory Perspective - Panjaitan, Roymon; Indriani, Farida (Media Ekonomi dan Manajemen, 2022)
This research intends to explore the experience of using brands in the past to increasingly love product brands through brand gravity-resonance capability, especially in the competition of the multi-business product sector. The novelty of this study lies in the synthesis of brand gravity variables, and brand resonance provides the proposed brand gravity-resonance capability variables of the resource-advantage theory of competition proposition results. Data were collected from 499 small and medium-sized business respondents through the dissemination of questionnaires and interviews. The SEM-PLS technique analyzes data with a path mediated by brand gravity-resonance capability on brand love. The results showed that brand gravity-resonance capability successfully mediated the brand experience relationship in brand love and the direct connection of brand experience in the past, and brand gravity-resonance capability in brand love managed to increase the sense of brand love. The practical implications of the novelty of this variable provide improvements to MSME managers or businesses to resonate the value of digital aggressiveness, configure science, integrate customer systems, and be oriented towards the creation of new markets. Conceptual implications contribute as new conceptual models that can bridge negative experiences to result in a dynamic and competitive comparative advantage in the market.